Analysis of medical prescriptions dispensed at health centers in Belo Horizonte, Minas Gerais, Brazil - Francisco A. Acurcio; Edson Perini; Sérgia M. S. Magalhães; Leonardo G. Vieira Terceiro; José Maurício Vieira Filho; Karla E. O. M. Coutinho; Kênia V. Caldeira; Luiza H. P. Cabral; Maria Carmen F. Santos; Patrícia M. Abrantes; Simone A. Vale; Miraneide C. Souza
This article focuses on medical prescriptions dispensed at health centers under the Municipal Health Department in Belo Horizonte, Minas Gerais State, Brazil. The study analyzed 4,607 prescriptions from March to April 1999, grouped according to origin (internal or external). The analysis focused on information written on medical prescriptions. The main findings were: (a) an average of 2.4 drugs per prescription in both groups; (b) prescriptions filled out with 4 or more drugs accounted for 18.0% of internal and 17.6% of external prescriptions; (c) 84.3% of internal and 85.5% of external prescriptions provided no instructions for use of medication; (d) information on dosage regimen varied from 51.2% to 97.6% for internal and 57.9% to 96.5% for external prescriptions; (e) generic names were specified for 51.9% and 28.4% of all drugs on internal and external prescriptions, respectively; (f) prescriptions containing standard drugs from the Municipal Health Department accounted for 88.7% of internal and 76.4% of external prescriptions. Data analysis shows the need for continuing education of physicians and adoption of other methods to improve quality of prescriptions and promote rational use of drugs.